2016
DOI: 10.13075/ijomeh.1896.00578
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between personality, emotional labor, work engagement and job satisfaction in service professions

Abstract: Objectives: Although there have been studies linking personality to selected aspects of functioning at work, Polish literature reports a shortage of detailed analyses considering, e.g., specific professional groups or certain variables. The aim of our study was to explore the links between personality traits and emotional labor, work engagement and job satisfaction among service workers. Material and Methods: The study was based on a cross-sectional, self-report survey of 137 workers representing different ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 53 publications
3
38
1
3
Order By: Relevance
“…In her seminal work on emotional labour, she argues that employees have to trade-off their emotional expressions for a wage, and hence, engagement in emotional labour is demanding. Other recent studies (Dursun, Bayram & Aytaç, 2011;Grandey, Diefendorff, & Rupp, 2013;Mróz & Kaleta, 2016) have also confirmed emotional labour as a process of regulating emotional expressions in order to meet organizational goals. In relation to nursing, nurses are expected to show positive emotions including empathy towards patients/clients even when patients/clients show negative emotions such as anger.…”
Section: Introductionmentioning
confidence: 79%
“…In her seminal work on emotional labour, she argues that employees have to trade-off their emotional expressions for a wage, and hence, engagement in emotional labour is demanding. Other recent studies (Dursun, Bayram & Aytaç, 2011;Grandey, Diefendorff, & Rupp, 2013;Mróz & Kaleta, 2016) have also confirmed emotional labour as a process of regulating emotional expressions in order to meet organizational goals. In relation to nursing, nurses are expected to show positive emotions including empathy towards patients/clients even when patients/clients show negative emotions such as anger.…”
Section: Introductionmentioning
confidence: 79%
“…Core self-evaluation shows a strong relationship with JS [8,9], effective nursing work environments [10], work success [11], nurses' job stress [12] and turnover intentions [13]. One of dimension of CSE, neuroticism, proved to be the most significantly related with JS [14]. Apart from the connection of CSE and JS, many studies have shown possible mediators that may explain why CSE is associated with dimensions of JS and job outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Yukarıda ki özet tabloda da yer aldığı gibi; duygusal emek kavramına ilişkin çalışmalar, odak noktası açısından faklı boyut ve modellere sahip olup, çalışma kapsamında duygusal emeğin yüzeysel davranış, derinlemesine davranış ve doğal (samimi) davranış olmak üzere üç boyutu esas alınmıştır. Yüzeysel davranış; çalışanın görevini icra ederken bireysel duygularının değişmemesine ve isteksiz olmasına rağmen olumlu ve güler yüzlü bir ifade takınması, gerçek hislerini saklaması, sahte duygular sergilemesidir (Mroz ve Kaleta, 2016, Grandey, 2000, Kim ve diğerleri, 2017. Yüzeysel davranış; suçluluk duygusu, memnuniyetsizlik, daha az müşteri memnuniyeti, daha az hizmet kalitesi şeklinde sonuçlara neden olmaktadır (Groth ve diğerleri, 2009, Guillaume, 2015.…”
Section: Duygusal Emek Kavramıunclassified